Pengaruh Variasi Metode Mengajar Guru PAI Terhadap Motivasi Belajar Siswa Kelas Viii Semester Genap SMPN 3 Satu Atap Siliragung Banyuwangi Tahun Pelajaran 2015/2016 - Eko Budiywono (IAI Darussalam, 2017)
This research aims to: Knowing the variety of teaching methods PAI teacher second semester of class VIII SMPN 3 years Siliragung One Roof lessons 2015/2016, (2) motivation Mengeahui class VIII student of SMPN 3 Siliragung second semester One roof in the school year 2015/2016, (3) the effect of variations of PAI teacher teaching methods to motivate students of class VIII SMPN 3 Siliragung One roof Banyuwangi year 2015/2016 lesson. In this research using quantitative descriptive, method product moment. The population of this research is class VIII SMPN 3 Siliragung One Roof numbering 49. After analyzing the data collected, it was found that (1) the variation of teaching methods PAI teacher SMPN 3 Siliragung One Roof is very good. (2) Motivation class VIII student of SMPN 3 Siliragung One Roof is very good. (3) There is a variety of teaching methods influence on the motivation of teachers PAI class VIII student of SMPN 3 Siliragung second semester One Roof Banyuwangi by 36.3%